Antagonisme In-Vitro Lima Isolat Lokal Trichoderma spp. Asal Rhizosfer Terhadap Rhizoctonia solani Penyebab Busuk Pelepah Jagung - Soplanit, Rainhart C; Patty, Jogeneis; Talahaturuson, Abraham (Universitas Pattimura, 2021)
Environmentally friendly biological control can be an alternative for suppressing the pathogen Rhizoctonia solani, the cause of sheath rot in corn plants. This can be done by utilizing biological agents, such as Trichoderma spp. Research on in vitro antagonism of five local isolates of Trichoderma spp. of rhizospheric origin against R. solani was carried out at the Plant Disease Diagnosis Laboratory, Faculty of Agriculture Unpatti, Ambon. This research aimed to determine the inhibition of five Trichoderma spp isolates against R. solani in vitro and to the mechanism of its inhibition. This study used a Completely Randomized Design to test the five local isolates of Trichoderma spp. The experiment was carried out with 4 replications, and each experimental unit consisted of 2 Petri dishes for testing. The results showed that the five local isolates of Trichoderma spp. from the rhizosphere could suppress the growth of R. solani on corn plants in vitro. On the seventh day of observation, the highest inhibition occurred in Trichoderma isolate from the Banda Baru coconut rhizosphere (TrichoRKlBB), which was 100% and the local Trichoderma isolate rhizosphere of Nuruwe cocoa (TrichoRKN) 100%, and the lowest percentage occurred using the Trichoderma isolate rhizosphere of Waisamu coconut (TrichoRKlW), namely (80.13%). The mechanisms of antagonism that occured were the mechanisms of competition and microparasitism.